Optimizing the Design and Analysis of Clinical Trials for Antibacterials Against Multidrug-resistant Organisms: A White Paper From COMBACTE's STAT-Net. (13th August 2018) - de Kraker, Marlieke E A; Sommer, Harriet; de Velde, Femke; Gravestock, Isaac; Weiss, Emmanuel; McAleenan, Alexandra; Nikolakopoulos, Stavros; Amit, Ohad; Ashton, Teri; Beyersmann, Jan; Held, Leonhard; Lovering, Andrew M; et al.
Abstract: Innovations are urgently required for clinical development of antibacterials against multidrug-resistant organisms. Therefore, a European, public-private working group (STAT-Net; part of Combatting Bacterial Resistance in Europe [COMBACTE]), has reviewed and tested several innovative trials designs and analytical methods for randomized clinical trials, which has resulted in 8 recommendations. The first 3 focus on pharmacokinetic and pharmacodynamic modeling, emphasizing the pertinence of population-based pharmacokinetic models, regulatory procedures for the reassessment of old antibiotics, and rigorous quality improvement. Recommendations 4 and 5 address the need for more sensitive primary end points through the use of rank-based or time-dependent composite end points. Recommendation 6 relates to the applicability of hierarchical nested-trial designs, and the last 2 recommendations propose the incorporation of historical or concomitant trial data through Bayesian methods and/or platform trials. Although not all of these recommendations are directly applicable, they provide a solid, evidence-based approach to develop new, and established, antibacterials and address this public health challenge. Abstract : Innovations are urgently required for clinical development of antibiotics against multidrug-resistant organisms. COMBACTE-STAT-Net provides recommendations for improved pharmacokinetic-pharmacodynamic modeling, more sensitive primary end points, hierarchical nested-trial designs, and use of historical/concomitant trial data through Bayesian methods and/or platform trials.